Penerapan Metode Long Short-Term Memory Pada Pendataan Warga Berbasis Android - Sri Lestari; Muhammad Fakhri Pratama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Along with technological developments, utilization in data processing both input and output become very important. Starting from inputting data manually, it proves that the use of technology is still not fully used. Data that has been processed conventionally sometimes encounters problems caused by human error. Not only that, when data must be entered into a computer, it requires additional time and when natural disasters such as floods, earthquakes, landslides occur. Census files that are still in the conventional form are likely to be damaged and will take time to re-data. This is the main reason for RT 004 RW 008 to need an efficient data collection system. The application of Optical Character Recognition (OCR) technology in this study is expected to be a solution in increasing the efficiency of the data input process. In this study, the input process is carried out in real time using the Long Short-Term Memory (LSTM) method to scan data on e-KTP. The results of testing OCR technology with the LSTM method in this study for the three experiments carried out were 1) The e-KTP detection experiment resulted in an accuracy of 100%, 2) The trial of reading 19 attributes on the e-KTP resulted in an accuracy of 98.42%, 3) Testing the error reading of the e-KTP attribute resulted in an accuracy of 93.56%. Overall, the accuracy of the LSTM method in word detection on e-KTP results in an accuracy of 92.1%. These results indicate that the application of OCR technology with the LSTM method is one of the right solutions for the data input process.